ETLEN, a Linguistic Atlas of the Boundary between Galician-Portuguese and Asturleonese in Asturias (Spain) - d’Andrés, Ramón (Madrygal. Revista de Estudios Gallegos, 2019)
ETLEN is a new linguistic atlas centered on a linguistic boundary area, which separates the Galician-Portuguese and Asturleonese domains in westernmost strip of Asturias. The data source is an own survey in 40 localities of the territory. In addition to a dialectographic section or conventional dialectal cartography (531 maps corresponding to as many isoglosses), it includes two novel sections of statistical cartography: horiometric or of geotypological ascription of the geovariants (35 maps); and dialectometric or of measurement of similarities between the localities of the territory (77 maps).
Keywords: Linguistic Atlas; Galician-Portuguese; Asturleonese; Horiometry; Dialectometry